THIN-WALLED POTTERY FROM AN EARLY IMPERIAL COMPLEX AT PRIENE/IONIA - Fenn, Nina (Rei Cretariae Romanae Fautorum Acta, 2024)
For the first time a sizeable spectrum of thin-walled pottery from the current excavations at Priene will be presented, material which is – with exceptions – not known from the earlier excavations in the 19th century. While in late-Hellenistic times the occurrence of thin-walled pottery at Priene seems to be restricted to sporadic imports from Italy, quantities of locally or regionally produced thin-walled drinking vessels increase in the early-Imperial period.